Pancreatic adverse events in patients treated with immune checkpoint inhibitors. Issue 3 (6th February 2023) - Hana, Caroline; Rehman, Tauseef; Park, Kyeeun; Carracedo Uribe, Carlos; Aung, Pyi Phyo; Hunis, Brian; Salzberg, Matthew; Zikria, Jennifer; Hussein, Atif
Abstract: Background and Aim: The inhibition of cytotoxic T‐lymphocyte associated antigen‐4 (CTLA‐4) and programmed cell death‐1 (PD‐1) has been a target for multiple drugs to enhance the T‐cell antitumor activity. However, these immune checkpoint inhibitors (ICIs) come with a panel of immune‐related adverse events (irAEs) that include mainly endocrine, skin, and gastrointestinal effects. We report seven cases of pancreatic irAEs in patients treated with ICIs at our institute. Methods: This is a case series; data was collected through chart review by 3 different data collectors and was analyzed separately by 2 physicians. Results: Of these seven cases, two had diabetic ketoacidosis (DKA), while five had pancreatitis diagnosed by a substantial rise in serum lipase. Pancreatitis was asymptomatic in two cases. A pancreatic biopsy in one case revealed type 2 autoimmune pancreatitis. The ICIs used included pembrolizumab, nivolumab, durvalumab, and avelumab. Treatment included steroids and holding the ICI therapy: three cases had complete resolution of pancreatitis while two cases required either a prolonged taper or a second course of prednisone for recurrence of pancreatitis. On the other hand, the DKA cases were treated with withdrawal of the ICI and starting insulin with no steroid therapy. Conclusions: Pancreatitis and DKA are rare adverse events of ICIs that can be controlled by holding the ICI with or without starting steroids. Rechallenging the patient with the same ICI is possible in selected cases. Abstract : This case series identifies seven patients treated with immune checkpoint inhibitors at Memorial Cancer Institute, who developed the rare pancreatic endocrine and exocrine immune‐related adverse events (irAEs). It highlights their outcomes and discusses some possible predisposing factors for such irAEs.